Assessment of the web application security effectiveness against various methods of network attacks - Erbel, Mateusz; Kopniak, Piotr (Journal of Computer Sciences Institute, 2018)
The article discusses the issue of the security of Internet applications. The most popular types of attacks and methods of securing web applications against them are discussed. The study conducted the effectiveness of security of web applications. The research methodology was based on the proprietary application implemented in PHP technology. The result of the research is a proposal of solutions aimed at improving application security.